Solar Powered Smart Irrigation System - Sardesai Mayur A.; Patil Ranjeet G.; Dr. Irrana Korachgoan; Katkar Kiran B. (International Journal of Innovations in Engineering Research and Technology, 2021)
Agricultural sector is backbone of Indian economy as population increases demand ofwater also increases. Usually lots of water wastage takes place in the land, due to improper method of irrigation. A solar-based smart irrigation system enables user to monitor the relative soil moisture at many different location throughout the field to more precisely scheduled irrigation cycle. By using solar energy, we can save the electrical energy. The sensing system is based on feedback control mechanism with microcontroller unit depending upon the varied requirement of different crops we can irrigate our field.